DAMPAK INVESTASI PENDIDIKAN TERHADAP PEREKONOMIAN DAN KESEJAHTERAAN MASYARAKAT KABUPATEN DAN KOTA DI JAWA TENGAH - Sulistyowati, Niken; Harianto, Harianto; Priyarsono, D S; Tambunan, Mangara (Jurnal Organisasi dan Manajemen, 2010)
The objectives of the research are: (1) to analyze the influence of increasing education (years of schooling) on labor productivity in agriculture, industry and service of districts and municipalities in Central Java, (2) to analyze the impact of increasing education expenditure policy on economic performance and people welfare. The result of the research shows that the increasing of education in agriculture sector is effective strategy to increase labor productivity in agriculture sector. In the long run, the increasing of education is effective to improve labor productivity in all sectors. The increasing of education expenditure policy could improve local economic performance and people welfare, which is indicated by increasing of human capital accumulation, sectoral labor productivity, sectoral labor demand, gross regional domestic product, government revenue, government expenditure, household expenditure, investment, household expenditure per capita, decreasing of unemployment, inequity and poverty.